2013
DOI: 10.4172/2325-9639.1000119
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems, Suicidality and Depression among American Indian Youth

Abstract: Study background Mental health and sleep problems are important public health concerns among adolescents yet little is known about the relationship between sleep, depressive symptoms, and suicidality among American Indian youth. Methods This study examined the impact of sleep and other factors on depressive symptoms and suicidality among Lumbee American Indian adolescents (N=80) ages 11–18. Results At the bivariate level, sleepiness, was associated with depression but not with suicidality. Time in bed (TIB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Table 1 presents a summary of sample descriptions, prevalence and correlates of insufficient sleep and insomnia, the measures used, and author recommendations for the 12 articles included in this review. The limited research literature focused on the following aspects of insufficient sleep and insomnia: (1) prevalence [20, 46–52], (2) demographic and cultural correlates [20, 46, 4850, 5355], (3) medical and mental health correlates and predictors [4653, 55], and (4) theoretical mechanisms for the insufficient sleep-culture-chronic disease relationships [4749].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 presents a summary of sample descriptions, prevalence and correlates of insufficient sleep and insomnia, the measures used, and author recommendations for the 12 articles included in this review. The limited research literature focused on the following aspects of insufficient sleep and insomnia: (1) prevalence [20, 46–52], (2) demographic and cultural correlates [20, 46, 4850, 5355], (3) medical and mental health correlates and predictors [4653, 55], and (4) theoretical mechanisms for the insufficient sleep-culture-chronic disease relationships [4749].…”
Section: Resultsmentioning
confidence: 99%
“…Insufficient sleep and insomnia also had differences in associations between depression and suicide: a study of 80 AI adolescents found less time in bed to be associated with increased odds of self-reported suicidality but not depression among AI adolescents [55]. A dissertation study using a sample of 232 students, ages 12–21, found insomnia to be a predictor of depression but not suicidal ideation or suicide attempts among AI/AN youth [52].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not statistically significant, participants with regular attendance (at least two thirds of classes) showed a decrease in suicidal ideation and increase in protective factors. Significant findings are limited due to the small sample size and lack of randomization; topical results on bullying (Bell et al, 2014) and depression and nonsuicidal self-harm (Arnold et al, 2013) are presented elsewhere. Culture class evaluation data supported program importance and was used by the tribe to support the continuing need for youth-focused programs.…”
Section: Discussionmentioning
confidence: 99%
“…However, sleep has not been systematically evaluated in association with suicide risk specifically among AI/AN adults. In one study of AI youth, more time in bed was found to be associated with suicidality and depressive symptoms [ 23 ].…”
Section: Introductionmentioning
confidence: 99%